Revisiting the Therapeutic Effects of Essential Oils on the Oral Microbiome - Casandra-Maria Radu; Carmen Corina Radu; Sergiu-Alin Bochiș; Emil Marian Arbănași; Alexandra Ioana Lucan; Viorela Romina Murvai; Dana Carmen Zaha (MDPI AG, 2023)
The extensive use of antibiotics has resulted in the development of drug-resistant bacteria, leading to a decline in the efficacy of traditional antibiotic treatments. Essential oils (EOs) are phytopharmaceuticals, or plant-derived compounds, that possess beneficial properties such as anti-inflammatory, antibacterial, antimicrobial, antiviral, bacteriostatic, and bactericidal effects. In this review, we present scientific findings on the activity of EOs as an alternative therapy for common oral diseases. This narrative review provides a deeper understanding of the medicinal properties of EOs and their application in dentistry. It not only evaluates the effectiveness of these oils as antibacterial agents against common oral bacteria but also covers general information such as composition, methods of extraction, and potential toxicity. Further nonclinical and clinical studies must be conducted to determine their potential use and safety for treating oral diseases.